MYCOFLORA OF FERMENTED LOCUST BEANS (Parkia biglobosa) SEED, “IRU” SOLD IN LOKOJA MARKETS, KOGI STATE, NIGERIA - Okolo, Esther; Simon, Victory Ojoene; Eze, M. E. (FUDMA JOURNAL OF SCIENCES, 2023)
Fermented locust beans are a popular nutritious food seasoning that are prone to microbial contamination due to unhygienic handling and improper storage. This research aimed to evaluate the mycological quality of locust beans sold in Lokoja markets, Kogi State, Nigeria. Thirty (30) samples of locust beans were collected from five different markets in Lokoja, analyzed for inherent fungi which were identified using standard mycological techniques. The results indicated variations in the mean fungal loads across the sampled markets. Old market had the highest mean fungal load (4.33 × 105 CFU/g), followed by Adankolo market (3.67 × 105 CFU/g) and Kpata market (3.0 × 105 CFU/g) while Lokongoma market had the lowest mean fungal load (2.0 × 105 CFU/g). The mean fungal load of the fermented locust beans from Old market was significantly different (p>0.05). A total of 55 fungal isolates that include: Aspergillus niger (29.1 %), Rhizopus arrhizus (25.5 %), Fusarium cladosporium (18.2 %), Fusarium cummunis (12.7 %), Aspergillus nudilans (9.1%), Aspergillus tamari (7.3 %) and Aspergillus terreus (1.8%) were obtained from the samples. Aspergillus niger, F. communis, F. clamadosporium and R. arrhizus were present in all the sampled markets, suggesting they are the predominant fermenter of locust beans. The presence of mycotoxigenic fungi in the locust beans seeds poses a significant public health risk. Therefore, it is important to ensure that locust beans are processed and stored under hygienic conditions at all times to safeguard consumer health.
Keywords: Locust beans; mycological quality; fungal contamination; public health risk